2018
DOI: 10.1097/iop.0000000000001105
|View full text |Cite
|
Sign up to set email alerts
|

Frontalis Muscle Flap Versus Maximal Anterior Levator Resection as First Option for Patients With Severe Congenital Ptosis

Abstract: Good functional and aesthetic results were obtained with both surgical techniques. FMF required fewer reoperations compared with maximal ALR, offering a better long-term result without residual ptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Lastly, recurrence is a potential complication of all frontalis suspension approaches. We observed a recurrence rate of 12.9% at postoperative time points of 5 months, 12 months, or 24 months and a previous long-term study reported a recurrence rate of 20% to 23% over 10 years 27,29 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Lastly, recurrence is a potential complication of all frontalis suspension approaches. We observed a recurrence rate of 12.9% at postoperative time points of 5 months, 12 months, or 24 months and a previous long-term study reported a recurrence rate of 20% to 23% over 10 years 27,29 …”
Section: Discussionsupporting
confidence: 74%
“…We observed a recurrence rate of 12.9% at postoperative time points of 5 months, 12 months, or 24 months and a previous long-term study reported a recurrence rate of 20% to 23% over 10 years. 27,29 This study has several limitations. It is retrospective in nature and as such patients were followed for varying postoperative intervals making it difficult to generalize the long-term durability of the effect.…”
Section: Discussionmentioning
confidence: 96%
“…The frontalis muscle, an important muscle tissue for raising the upper lid, works with the levator muscle to lift the upper lid, and plays an important role in cases of poor levator muscle strength. The frontal muscle flap belongs to the autologous tissue, which is not only rich in blood supply, but also has innervation and strong muscle strength, and because it is interwoven with the surrounding tissues, it is less prone to flap relaxation, which facilitates the ideal effect of frontal muscle flap repair, but can cause some damage to the patient’s frontal muscle strength after surgery ( 20 , 21 ). The present results showed that the frontal muscle strength of the affected side was higher in the observation group than in the control group at 1, 6 and 12 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been found that FMF may cause more examples of aesthetic and functional complications, which can be reduced with MLR. [ 25 26 ]…”
Section: Discussionmentioning
confidence: 99%